Understanding the Lexicon of Fatigue in Parkinson’s Disease - Mantri, Sneha (J Parkinsons Dis, 2020)
BACKGROUND: Fatigue in Parkinson’s disease (PD) is multifaceted and associated with reduced quality of life. In turn, the language used by people with PD to describe fatigue is variable and poorly understood. We sought to elucidate the lexicon of fatigue using a qualitative grounded theory approach. OBJECTIVE: The objective of this study was to understand how patients with PD describe fatigue. METHODS: A pre-study phase of online journaling (Phase 1) provided information regarding topics of importance to patients. Following this, two independent samples of fatigued subjects were studied. Individuals with PD participated in a telephone interview (Phase 2); interview transcripts were analyzed to develop a detailed codebook. To ensure trustworthiness of the findings, an online survey (Phase 3) was administered to individuals with self-reported PD participating in the online study Fox Insight. The survey included the following question: “How do you define fatigue? Please provide your definition in the space below.” The codebook developed from Phase 2 was applied to the Phase 3 responses. RESULTS: Fifteen individuals participated in Phase 2 and 413 individuals completed Phase 3. Fatigue was subdivided into three domains: cognitive, emotional, and physical. Nearly all individuals experienced more than one domain of fatigue. The most common themes included tiredness, lack of energy, and negative motivation. CONCLUSION: Fatigue in PD is multidimensional. Questionnaires that only assess the physical impact of fatigue may not be adequate to capture the broad range of experiences of fatigue among people with PD.